Anxiety and Depression as Predictors of Quality of Life among University Undergraduates - Fakrogha, Benita E; Olapegba, Peter O; Uye, Emmanuel Etim (Universitas Nurul Jadid, 2025)
Quality of life has remained a recurring theme in research considering it’s important in the overall psychological well-being of the individuals. Several predictors have been used to investigate quality of life among different populations and samples with varied results. Importantly, studies investigating undergraduate quality of life tend to be scarce. Therefore, this study investigated the predictive ability of anxiety and depression on quality of life among undergraduates in Ibadan, Nigeria. Cross-sectional research design was adopted while purposive sampling technique was used to select one university in South-west Nigeria. Data were conveniently collected from 400 undergraduates using validated scales and analyzed using zero-order statistics and multiple regression to test four hypotheses which was accepted at p = .001). The results demonstrated that anxiety and depression jointly and independently predicted the physical, psychological, social relationship and environment domain quality of life among study participants. The study concludes that anxiety and depression are robust predictors of quality of life among the population of study. The study recommended that parents and other stakeholders should work in synergy to reduce triggers of anxiety and depression and provide for the well-being of the undergraduates.